Haversine Algorithm-Based GIS for Nearest Health Facility Mapping in Bekasi Regency - Andy Achmad Hendharsetiawan; Dwipa Handayani (LPPM Universitas Islam 45 Bekasi, 2026)
The uneven distribution of healthcare facilities in Bekasi Regency makes it difficult for the public to find the nearest services. This study aims to design a Geographic Information System (GIS) to map and find routes to the nearest healthcare facilities. The system implements the Haversine algorithm to calculate the shortest distance precisely based on coordinate points accounting for the earth's curvature. Software development uses the adaptive Extreme Programming (XP) method. System functionality testing was conducted using the Black Box Testing method. The test results indicate that all features on the admin and user interfaces function optimally. In conclusion, integrating the Haversine algorithm into this GIS is proven accurate in recommending the nearest locations, resulting in a practical mobile-based application that facilitates the general public.